(untitled) (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2025)
This article explores the role of national values in youth education and analyzes scientific and methodological approaches to their formation. The research is based on a systemic perspective, viewing values and upbringing as interrelated pedagogical categories. The necessity of integrating national values into modern education through interactive and innovative methods is substantiated. Methodical recommendations are proposed to enhance the effectiveness of the educational and moral development process.